Repair of ruptured abdominal aortic aneurysms with bifurcated endografts: a single-center study - Queiroz, André Brito (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2014)
OBJECTIVE: The aim of this study was to describe our early experience in the treatment of ruptured abdominal aortic aneurysms with bifurcated endografts. We report on our initial twelve-month experience using this approach. METHODS: Clinical data on patients with ruptured abdominal aortic aneurysms treated at a single tertiary center in Brazil were prospectively recorded. The eligibility for endovascular treatment was evaluated by computed tomography scanning and anatomical features were determined based on the method of treatment. RESULTS: From February 2012 to January 2013 (12 months), 28 consecutive patients (mean age 67.2 years, range 45-85 years) underwent treatment for ruptured abdominal aortic aneurysms at our hospital. Eighteen patients (64.3%) were suitable for and underwent endovascular treatment with bifurcated endografts (16 patients) or aortouniiliac endografts (two patients). Ten patients who were considered unsuitable for endograft repair underwent open repair. Seven patients were classified as hemodynamically unstable (Endovascular, 5; Open, 2), and 21 were classified as stable (Endovascular, 13; Open, 8). The overall 30-day mortality rate associated with endovascular treatment was 27.8% (stable, 18.7%; unstable, 40%) and the rate associated with open repair was 50% (stable, 37.5%; unstable, 100%). CONCLUSIONS: In this study, the suitability of patients for endovascular repair of ruptured abdominal aortic aneurysms was high and the overall results of endovascular treatment remain encouraging. Indeed, bifurcated endografts are a feasible option for treating anatomically eligible ruptured abdominal aortic aneurysms.